A development of an automated system for the transportation and cutting of raw glass using a suction gripper and a Fletcher cutter with a KUKA robot - Salazar, Hector (2023)
Currently, industries need to reduce production times, eliminate the possibility of human errors, and increase company profits. However, this is quite challenging since operators, working long hours each day, are prone to making mistakes due to fatigue or the use of outdated techniques. Taking this into account, this paper proposes the development of a hybrid suction and cutting gripper utilizing a Fletcher cutter attached to a KUKA KR60 robot responsible for cutting and transporting raw glass. The robot's motion is programmed using Kuka Sim Pro, while the design and stress analysis of the hybrid gripper were performed in Inventor. The result was an automated system capable of achieving cuts with a precision of 0.025 mm and a speed ratio of approximately twenty cutting and transportation processes per hour.